Foreign Policy Making in Colombia the Influence of Non-State Actors - Alviz Hernandez, Maria Alejandra (2015)
This study is titled Colombia Foreign Policy Making: the influence of non-state actors and its main purpose is to analyze the influence of Non-State actors, violent type and Human Rights NGOs, in the Colombian Foreign policy behavior. It is divided into three respective sections -- a Constructive theoretical framework, the directions of the Colombia Foreign Policy, and the practical part to find the influence of Non-state actors in Colombia Foreign Policy behavior. It strives to answer how Colombian Foreign Policy behavior it's affected by Violent Non-state actors negatively and by Human Rights NGOs.